Managing Infodemics in the 21st Century Addressing New Public Health Challenges in the Information Ecosystem - Purnat, Tina D.; Nguyen, Tim; Briand, Sylvie (Springer International Publishing : Imprint: Springer, 2023)
This open access book on infodemic management reviews the current discussions about this evolving area of public health from a variety of perspectives. Infodemic management is an evidence-based practice underpinned by the science of infodemiology that offers guidance to better manage pandemic and epidemic risks and more quickly tackle new and resurgent health threats. Infodemic management has added much visibility and recognition for the importance of social-behavioural sciences, health communication, participatory and human-centered approaches, and digital health as complementary scientific and practical approaches that also must be strengthened in public health practice through a whole-of-society and whole information ecosystem approach. This volume makes a case that health of the information ecosystem in the digital age has emerged as the fourth ecosystem that public health is challenged by, along with the triad of environment-human-animal health. The book brings together scientists and practitioners across disciplines to offer insights on infodemic management. The tools, methods, analytics, and interventions that they discuss in the context of acute health events also can be applied to other public health areas. Topics covered include: People's Experience of Information Overload and Its Impact on Infodemic Harms Smart Health! Expanding the Need for New Literacies To Debunk or Not to Debunk? Correcting (Mis)information Partnering with Communities for Effective Management of Health Emergencies Managing Infodemics in the 21st Century is required reading for public health practitioners in need of an overview of this evolving field of practice that has made major scientific and practical leaps forward since early 2020. Global, regional, and local health authorities are increasingly recognizing the need to expand their capacities for infodemic management in their efforts to better prepare for future health emergencies. This book is the resource they need to build toward a mature infodemic management process. The text also can be used as supplemental reading for graduate programs and courses in public health.